Digital economy and carbon emissions: spatial spillover effect and industrial structure mediation effect in China - Chen, Yuxi; Liu, Jian (Technological and Economic Development of Economy, 2025)
The relationship between the digital economy and carbon emissions has emerged as a critical issue in the pursuit of the Sustainable Development Goals by 2030. This study examines the spatial spillover effects and the mediating role of industrial structure in this relationship using panel data from 285 prefecture-level cities in China between 2011 and 2022. Employing the Spatial Durbin Model (SDM) to capture spatial effects, stepwise regression and bootstrap tests for mediating effects, and the System Generalised Method of Moments (SYSGMM) to address endogeneity, the study reveals several key findings. First, the digital economy significantly increases carbon emissions with substantial spillover effects across regions. Second, carbon emissions exhibit both temporal and spatial dependence, influenced by time and location, with emissions in neighboring areas having a significant impact, leading to a “snowball” effect. Third, the digital economy indirectly elevates carbon emissions by optimizing industrial structures. These findings underscore the need for comprehensive strategies to manage carbon emissions effectively during economic transformation, aiming towards an environmentally sustainable economy.First publihed online 02 April 2025